Contributions of the PPIP in the training of licensors in basic education : challenges and opportunities. (2022)
This reflection article shows the analysis of Educational Research of Detailing in the training of teachers in the Bachelor’s in Basic Education during the second semester of 1918. This paper presents the performance of the teachers in different educational contexts in which the Program is offered. It is important to highlight that the program has more than thirty years of experience in the training of Graduates in the country, where the teachers show their skills acquired throughout their professional training, according to the needs of the educational contexts with which they are faced.